Effects of modeling and imagery type on performance and learning of the volleyball simple serve - Bagherpour, T.; Shojaei, M. (International Journal of Sports Science and Engineering, 2009)
Imagery and modeling are similar cognitive processes that have been found to enhance performance. However, some imagery studies have shown a model of correct performance before beginning imagery to ensure that subjects are imagining the skill correctly; thus, confounding modeling and imagery. In a study that separated these factors, imagery type was not controlled. Therefore, the purpose of the present study was the comparison of the effect of modeling, internal imagery, and external imagery on performance and learning of volleyball simple serve using a pretest - posttest randomized - groups design. 48 novice female students with average imagery ability were randomly selected and matched in 4 groups based on self - efficacy (control, modeling, internal and external imagery). Data of from and result of performance were analyzed by 4*3 ANOVA with repeated measures of test factor and paired t test post hoc test. Results indicated that the result and from of performance of modeling group and after that internal imagery were significantly better than external imagery and control groups in last of acquisition, retention and transfer tests; but there were not significant differences between the from of performance of internal and external imagery groups in these tests. These findings suggest that modeling is more effective than internal and external imagery for individuals first learning a relatively simple, closed and discrete motor skill.